Hadith #3577 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Anas ibn Malik; Bilal ibn Ribah; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan Abi Dawud)
Two men from the locality of Kindah came while AbuMas’ud al-Ansari was sitting n a circle. They said: Is there any man who decides between us. A man from the circle said: I, AbuMas’ud took a handful of pebbles and threw at him, saying: Hush! It is disapproved to make haste in decision.
Grade: Da'if